2012
DOI: 10.1097/aud.0b013e3182263460
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic and Behavioral Outcomes of Cochlear Implantation in Children With Auditory Nerve Hypoplasia

Abstract: : Evoked responses recorded in CI children with AN hypoplasia indicate a high incidence of nonauditory activity with CI use. The range of abnormal responses was not predicted by the severity of the hypoplastic AN or associated structures. This, along with poorer auditory development compared with peers with normal AN diameters, suggests that children with hypoplasia of the AN are poor candidates for cochlear implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 64 publications
4
52
1
3
Order By: Relevance
“…The detection of an electrically generated ABR has been suggested as a test for candidacy assessment in cochlear nerve hypoplasia [Nikolopoulos and Kiprouli, 2004]. However, our observations on the efficacy of cochlear implantation in children with cochlear nerve hypoplasia do not support cochlear implantation in such cases [Valero et al, 2012].…”
Section: Discussioncontrasting
confidence: 54%
“…The detection of an electrically generated ABR has been suggested as a test for candidacy assessment in cochlear nerve hypoplasia [Nikolopoulos and Kiprouli, 2004]. However, our observations on the efficacy of cochlear implantation in children with cochlear nerve hypoplasia do not support cochlear implantation in such cases [Valero et al, 2012].…”
Section: Discussioncontrasting
confidence: 54%
“…In order to be able to differentiate the beneficial information obtained from MRI and HRCT, Pagarkar et al [2011] suggested a combination of the diagnostic imaging tools with audiological tests for the evaluation of the integrity of the hearing nerve. Bilaterally deaf children with uni-or bilateral cochlear nerve aplasia/hypoplasia showed overall poorer results in comparison to their peers having other malformations, such as an enlarged vestibular aqueduct (EVA) [Buchman et al, 2011;Valero et al, 2012]. Therefore, the authors do not recommend CI surgery in SSD patients with proven CND in view of the anticipated poor outcomes which in turn may negatively impact bilateral hearing compared to the unaided condition.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, it was previously reported that children with hypoplasia or aplasia of the CN showed poor auditory performance after CI. 20,21 We found that the size of the CN was correlated with post-CI AO sentence test scores. However, there was only a weak correlation between the AO (post-CI minus pre-CI) sentence test scores and the size of the CN, which was not statistically significant.…”
Section: Auditory Performance and Cn Sizementioning
confidence: 93%